CHANGES OF SOCIAL AND CULTURAL LIFEOF HILL KHARIASOF MAYURBHANJ DISTRICT OF ODISHA IN EAST INDIA - Tudu, Fagu; Mohapatra, Ratnakar (International Journal of Psychosocial Rehabilitation, 2020)
The study of changes in social and cultural life of the Hill Kharias of Mayurbhanj in Odisha is an important aspect of the tribal development of India. Among the total existing 62 tribes of Odisha, 13 tribes are ethno-cultural primitive tribal groups (PTGs). Later, these 13 primitive tribal groups (PTGs), including the Hill Kharia tribe of Mayurbhanj in Odisha, have been identified by the Government of India as PVTGs. The Hill Kharias are mostly living in Jashipur as well as Karanjia Block areas of Mayurbhanj district of Odisha, and they were residing many years ago in the Similipal hill range. After movement slowly, they spread to other blocks of Maryubhanj district like Bisoi, Baripada, Suliapada, Shamakhunta, Morada, Udala, Koptipada, etc. The Hill Kharia people belong to the Sal clan organisation. Forest is the key source for their livelihood, and for that they should worship different trees like Sal trees (Sala gachha), some many different trees, and many others. The aim of this article is to highlight the development and change of the Hill Kharias of Mayurbhanj in respect of various aspects like their family life,educational, housing and settlement, health and hygiene,, village council, economic,religious practice,dance, etc. as far as practicable on the part of present authors. For the writing of this article, both the primary and secondary sources are methodologically used by the authors.